IN THE LATE 19TH AND EARLY 20TH CENTURIES FROM THE HISTORY OF BUKHARA OASIS FARMING CULTURE (Scientific journal of the Fergana State University, 2023)
In the article, the customs and rituals related to farming of the inhabitants of the Bukhara oasis in the late 19th and early 20th centuries are studied, and the respect and attention to them is very high in our national values ​​is analyzed based on the views of the scholars of the East. Currently, the reforms implemented to improve the status of agriculture in society are analyzed, and it is shown that the effectiveness of these reforms largely depends on our national values.